The impact of using advanced computer programs on the interior architectural design of the home أثر استخدام برامج الحاسوب المتقدمه في التصميم المعماري الداخلي للمسكن - Mohamed Abdel Hamed (JES: Journal of Engineering Sciences, 2025)
This study examines the evolution of advanced computer software in its various versions, stages, techniques, parametric design, algorithms, and BIM technologies, as well as their positive impacts, advantages, and the challenges they entail in enhancing interior design quality and, consequently, the quality of life within residential buildings. The study focuses on three-dimensional modeling technology and modern design and drafting software, highlighting their role in enhancing precision and detail in the design of interior spaces. Additionally, it reviews the benefits of employing virtual reality techniques and virtual tours to foster user engagement and facilitate design exploration before implementation, thereby reducing time and costs associated with modifications during the early stages of a project. The study concludes that advancements in computer software represent a fundamental shift in the field of interior design, contributing to increased work efficiency and improved experiences for both users and designers, which positively influences housing quality and enriches the residents' living experience. The study aims to promote the adoption of advanced digital tools in the design process while emphasizing the need to bridge the gap between traditional methods and modern software-based approaches. It also highlights the importance of integrating architects and all related professionals to acquire the necessary expertise for achieving sound design, stressing the imperative of involving architects in software development processes to ensure effective harmony between design and technical aspects. تتناول هذه الدراسة التطور الذي شهدته برمجيات الحاسوب المتقدمة بمختلف اصداراتها واطوارها وتقنياتها والتصميم البارامتري والخواريزمات وتقنيات BIM وتأثيرها الإيجابي ومميزاتها والتحديات التي تتضمنها في تحسين جودة التصميم الداخلي وبالتالي جودة الحياة في المبني . وتركز الدراسة على تكنولوجيا النمذجة ثلاثية الأبعاد وبرمجيات التصميم والرسم الحديثة، موضحةً دورها في تعزيز الدقة والتفاصيل في تصميم المساحات والفراغات الداخلية. كما تستعرض الدراسة فوائد استخدام تقنيات الواقع الافتراضي والجولات الافتراضية في تعزيز تفاعل المستخدم وتيسير استكشاف التصاميم قبل بدء التنفيذ، مما يسهم في تقليل الوقت والتكاليف الناتجة عن التعديلات خلال المراحل المبكرة من المشروع.وتخلص الدراسة إلى أن التطور في برمجيات الحاسوب يمثل تحولًا جوهريًا في مجال التصميم الداخلي، إذ يساهم في رفع كفاءة العمل وتحسين تجربة المستخدم والمصمم على حد سواء، مما ينعكس إيجابيًا على جودة المسكن ويُثري التجربة المعيشية للسكان. وتهدف الدراسة إلى تعزيز تبني الأدوات الرقمية المتطورة في العملية التصميمية، مع التأكيد على ضرورة سد الفجوة بين الأساليب التقليدية والأساليب المعتمدة على البرمجيات الحديثة. كما تسلط الضوء على أهمية التكامل بين المعماريين وكل  المتخصصين المرتبطين بالمجال المعماري لاكتساب الخبرات المطلوبه للوصول الي التصميم الجيد ، مشددة على ضرورة إشراك المعماريين في عمليات تطوير البرمجيات لضمان تحقيق انسجام فعال بين الجوانب التصميمية والتقنية.